2016
DOI: 10.7575/aiac.ijalel.v.5n.5p.197
|View full text |Cite
|
Sign up to set email alerts
|

A Pragmatic Cross-Cultural Study of Complaints Expressions in Jordan and England

Abstract: Research shows an increasing interest in the area of cross-cultural pragmatics due to the existence of diverse problematic pragmatic norms (Al-Khawaldeh and Zegarac, 2013). It has been found that identifying cross-cultural differences in linguistic expression and socio-pragmatic norms of communicative acts would help to reduce problems in cross-cultural communication (Meier, 2010). To the best of the researcher's knowledge, no study has been conducted to compare the linguistic expression of complaining by Jord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…A previous study by Meier (2010) found that identifying cross-cultural differences in linguistic expressions and pragmatic norms of the communicative act would help reduce cross-cultural communication problems. Al-Khawaldeh (2016) showed interest in investigating the cultural style and politeness strategies used by Jordanian native speakers of Arabic and native speakers of English to express complaints. He compared the linguistic…”
Section: Previous Cross-cultural Studiesmentioning
confidence: 99%
“…A previous study by Meier (2010) found that identifying cross-cultural differences in linguistic expressions and pragmatic norms of the communicative act would help reduce cross-cultural communication problems. Al-Khawaldeh (2016) showed interest in investigating the cultural style and politeness strategies used by Jordanian native speakers of Arabic and native speakers of English to express complaints. He compared the linguistic…”
Section: Previous Cross-cultural Studiesmentioning
confidence: 99%
“…Drawing on the above literature, to date, it seems that several research papers have addressed complaining strategies. Most of them tackled complaints in ordinary conversations, cross-cultural, and intra-language speech act realizations of complaining (see Al-Khawaldeh, 2016;Al-Shorman, 2016). However, these studies have not discussed complaints in the context of social media.…”
Section: Complaining In the Jordanian Contextmentioning
confidence: 99%